INOVASI TANAMAN HIAS BUAH LOKAL UNTUK MENINGKATKAN PRODUKTIVITAS MASYARAKAT DESA SUNGAI RENGIT - Sari, Tira Patma; Sunanda, Rahman; Hasmawati, Hasmawati; Fafikha, Wiwin Nafiatul; Salmah, Ninn Non Ayu (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM) STISIPOL Candradimuka, 2020)
Innovation is something new waiting to be popularized and can benefit the human body. Knowledge is invaluable for promoting innovation. Without knowledge, innovation doesn't show the signs it seems. Local fruit plants are types of fruiting plants or trees that grow naturally in the territory of Indonesia, generally cultivated by the community. Local fruit forms have various forms, such as soursop fruit, Durian fruit, banana and also jengkol. Original fruit plants can fight cancer, have anti-inflammatory, antioxidant, anti-diarrheal, analgesic properties and can cure many diseases. Local people have a lot of power over local fruit plants. We have to ensure its sustainability. The method used in this activity is direct observation to the field. Some fruit plants that are grown vegetatively are soursop, durian, jengkol and banana plants. As a result of this activity, the community gets benefits and knowledge in cultivating local fruit plants.